PEMECAHAN TANAH PERTANIAN DIBAWAH BATAS MINIMUM MELALUI JUAL BELI DIKAITKAN DENGAN PENERAPAN LANDREFORM DI KABUPATEN PADANG LAWAS UTARA - SAHRIAL AZHAR SIREGAR (PREMISE LAW JURNAL, 2015)
The studied problems are factors cause the fragmentation of agricultural land under the minimum limit at Regency of Padang Lawas Utara. In addition to what a law consequence and efforts that influences the law enforcement on prohibition of fragmentation of agricultural land under the minimum limit by buying and selling related to the land reform application. This research is conducted by empiric juridical approach, and the sample of this research is 48 persons from 16 villages at Regency of Padang Lawas Utara. The fragmentation of agricultural land under the minimum limit by buying and selling caused by the necessity to the society on the urgent interest for their survival such as for medicine bill, educational fee, pay the debt, etc. Furthermore, it is important to review the regulation in which the minimum limit is 2 hectare can not be implemented in present. Keywords : Minimum limit, Fragmentation, Agricultural land